(untitled) (LACCEI, 2024)
This paper is the result of a research work on the modeling and simulation of an alternative refrigeration system used for liquefaction in a liquefied natural gas (LNG) plant in Peru. The plant is located in Pampa Melchorita, Lima and is the first natural gas liquefaction plant in South America, which is exported worldwide. In this research we used the ProMax 5.0 process simulator that allowed us to model and simulate the base scenario approximating the real plant using composition, temperature and pressure variables established by the plant itself to obtain a high reliability of the results obtained. After this, an alternative scenario was developed, based on the real one, where the composition of the refrigerant mixture containing ethylene was changed to ethane to check if this new mixture was able to liquefy the natural gas. In this alternative scenario, the LNG achieves a temperature 1.8 °C lower than that of the base scenario, avoiding the import of ethylene from overseas by the plant.